The Calicophoron daubneyi genome provides new insight into mechanisms of feeding, eggshell synthesis and parasite-microbe interactions - Shauna M. Clancy; Mark Whitehead; Nicola A. M. Oliver; Kathryn M. Huson; Jake Kyle; Daniel Demartini; Allister Irvine; Fernanda Godoy Santos; Paul-Emile Kajugu; Robert E. B. Hanna; Sharon A. Huws; Russell M. Morphew; et al. (BMC Biology)
Abstract Background The rumen fluke, Calicophoron daubneyi, is the major paramphistome species infecting ruminants within Europe. Adult flukes reside within the rumen where they are in direct contact with a unique collection of microorganisms. Here, we report a 1.76-Gb draft genome for C. daubneyi, the first for any paramphistome species. Results Several gene families have undergone specific expansion in C. daubneyi, including the peptidoglycan-recognition proteins (PGRPs) and DM9 domain-containing proteins, which function as pattern-recognition receptors, as well as the saposin-like proteins with putative antibacterial properties, and are upregulated upon arrival of the fluke in the microbe-rich rumen. We describe the first characterisation of a helminth PGRP and show that a recombinant C. daubneyi PGRP binds to the surface of bacteria, including obligate anaerobes from the rumen, via specific interaction with cell wall peptidoglycan. We reveal that C. daubneyi eggshell proteins lack L-DOPA typically required for eggshell crosslinking in trematodes and propose that C. daubneyi employs atypical eggshell crosslinking chemistry that produces eggs with greater stability. Finally, although extracellular digestion of rumen ciliates occurs within the C. daubneyi gut, unique ultrastructural and biochemical adaptations of the gastrodermal cells suggest that adult flukes also acquire nutrients via uptake of volatile fatty acids from rumen fluid. Conclusions Our findings suggest that unique selective pressures, associated with inhabiting a host environment so rich in microbial diversity, have driven the evolution of molecular and morphological adaptations that enable C. daubneyi to defend itself against microorganisms, feed and reproduce within the rumen.